Water droplet evaporation in varied gravity and electric fields - O'Shaughnessy, Seamus; Robinson, Anthony; Gibbons, Michael (My University, 2024)
Sessile water droplet evaporation in varied gravity and electric fields has been experimentally studied. Specifically, the influences of gravity and electric fields are investigated in the context of the heat flux distribution beneath the droplets, as well as the droplet mechanics and resulting shapes. Experimental testing was carried out during a European Space Agency (ESA) Parabolic Flight Campaign (PFC 66). The droplets tested evaporated with a pinned contact line, a single wettability condition, and varied droplet volume and substrate heat flux. The peak heat transfer was located at the contact line for all cases. The peak heat flux, average heat flux, and droplet evaporation rate were shown to vary strongly with gravity, with higher values noted for hypergravity conditions and lower values in microgravity conditions. The droplet thermal inertia was shown to play a significant role, with larger droplets taking more time to reach thermal equilibrium during the parabolic testing period. No significant impact of the electric field on the droplet evaporation was noted for these test conditions.
PUBLISHED